TTP-like syndrome associated with hemoglobin SC disease treated successfully with plasma and red cell exchange. (2019) - Kodali, Sreenath; Ramachandran, Preethi; Richard, Ivan N.; Wang, Jen-Chin
Abstract: Background: Sickle cell hemoglobinopathies are associated with end organ damage but very rarely present with a clinical and laboratory picture of microangiopathic hemolytic anemia (MAHA) and thrombocytopenia, characteristic of thrombotic microangiopathy (TMA). Case presentation: We present a patient with HbSC disease who developed thrombotic microangiopathy, needing both RBC exchange transfusion and therapeutic plasma exchange (TPE) for complete clinical recovery. Conclusion: Although literature showed therapeutic plasma exchange alone can abrogate a similar clinical scenario, we did an in-depth review which concluded that in most of the TMA cases secondary to sickle cell disease, treatment with both with plasma exchange and red cell exchange transfusion are necessary.